Carbon composite wave-absorbing material and preparation method thereof

By soaking the alkali solution, water bath treatment, magnetic metal salt solution and high temperature sintering material, prepare carbon composite suction materials, solve the problem of waste filter cotton, and achieve high value -added use and excellent microwave. Absorption performance.

CN119383939AActive Publication Date: 2025-01-28HEFEI UNIV OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411621895.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-28
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively deal with waste filter cotton, which leads to environmental pollution and health hazards. At the same time, the waste gas and waste slag generated by high-temperature incineration also cause harm to the environment.

Method used

Use an alkaline solution to soak and water bath to treat waste filter cotton. After removing surface glue, it is soaked into a magnetic metal salt solution, and then sintering is made of carbon composite suction material.

Benefits of technology

The high value -added utilization of scrap cotton is realized, reducing the harm to the environment and human health, and at the same time, the prepared carbon composite suction material has excellent microwave absorption performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119383939A_ABST
    Figure CN119383939A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of wave-absorbing materials, and particularly relates to a carbon composite wave-absorbing material and a preparation method thereof. The waste filter cotton is degummed to serve as a carbon source, the pretreated waste filter cotton is impregnated in magnetic metal salt by adopting an impregnation method, and then heat treatment is performed to obtain the composite wave-absorbing material. A carbon skeleton formed after the waste filter cotton is subjected to heat treatment forms a conductive network in the composite material, and the composite material has good dielectric loss. The magnetic metal elementary substance and the alloy thereof have high saturation magnetization and provide magnetic loss in the composite material. Through the synergistic effect of dielectric loss and magnetic loss, the problem of poor impedance matching of a single carbon material is solved. The preparation process is simple and pollution-free, solves the problem of environmental pollution caused by treating the waste filter cotton by a traditional method, and is easy for large-scale production. The prepared composite wave-absorbing material is light in weight, efficient, good in impedance matching and excellent in wave-absorbing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wave absorbing materials, and in particular relates to a carbon composite wave absorbing material and a preparation method thereof. Background Art

[0002] With the change of seasons, EMU air conditioners, car air conditioners, household air conditioners and commercial air conditioners are frequently used, generating a large amount of solid waste of waste filter cotton. Waste filter cotton has a fiber network skeleton structure, and its main component is polyester fiber, which is a high molecular waste and is not easy to break. It is easy to produce a large amount of smoke and harmful gases when burned in the air. A large amount of waste filter cotton, stacked and stored, occupies space, not only affects the environment, but also poses a hidden danger to the safety management of light floating objects. Therefore, a scientific, effective and harmless method is needed to treat waste filter cotton to avoid its impact on the environment and human health and realize resource recycling.

[0003] At present, the way to deal with waste filter cotton is to send it to a recycling and processing agency for treatment. These methods mainly include mechanical separation and high-temperature incineration. Among them, the mechanical separation method is to reprocess and utilize the fiber materials in the waste filter cotton, but the comprehensive utilization rate of the waste filter cotton is not high, and it is mainly concentrated in the application of low value-added products. The high-temperature incineration method is to use high temperature to burn the combustible substances in the waste filter cotton, and then landfill the waste residue produced by the combustion, but the waste gas and waste residue produced by the high-temperature incineration method will cause certain harm to the environment. Therefore, while seeking harmless treatment and reuse of waste filter cotton, multiple aspects such as rationality, safety and high added value should be comprehensively considered.

[0004] With the rapid advancement of information technology, the electromagnetic interference and radiation generated by wireless communication devices have posed a certain threat to human health. Absorbing materials can convert electromagnetic radiation into heat energy, etc., effectively weakening the impact of electromagnetic waves. They have attracted much attention because they can effectively protect human health and ensure the normal operation of electronic equipment. In recent years, carbon-based composites have been regarded as promising microwave absorbing materials because of their low density, high conductivity and a large number of interface advantages, which can efficiently absorb electromagnetic waves. Despite its many benefits, the expensive and complex synthesis process of carbon materials (such as graphene, carbon nanotubes, etc.) severely limits their large-scale application.

[0005] In summary, if a solution is designed to use waste filter cotton as raw material to prepare low-cost and high-value-added absorbing composite materials, it will be of great significance to avoid the harm of waste filter cotton to the environment and human health and realize the high-value resource utilization of waste filter cotton. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a carbon composite microwave absorbing material. The method can recycle waste filter cotton, achieve high added value utilization, reduce harm to the environment and human health, and has excellent microwave absorption performance.

[0007] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a carbon composite absorbing material, comprising the following steps:

[0008] S1, cutting the waste filter cotton into small pieces, soaking it in an alkaline solution and treating it in a water bath, then taking out the treated waste filter cotton, washing it with deionized water several times until it is neutral, and drying it to obtain pretreated waste filter cotton;

[0009] S2, prepare a magnetic metal salt solution, add the pretreated waste filter cotton, let it stand and soak evenly, then take it out and dry it to obtain a precursor;

[0010] S3. Place the precursor in a protective atmosphere, sinter at 600°C-900°C for 1-2 hours to obtain a composite absorbing material.

[0011] As the preparation method of carbon composite absorbing material is further improved:

[0012] Preferably, the alkaline solution is one of sodium hydroxide and potassium hydroxide, and the concentration is 5wt%-10wt%.

[0013] Preferably, the water bath temperature is 80-100°C for 6-10 hours, and the drying temperature is 40-80°C for 4-10 hours.

[0014] Preferably, the concentration of the magnetic metal salt is 0.1-1 mol / L, and the amount of pretreated waste filter cotton added to the magnetic metal salt solution is 0.01-0.1 g / ml.

[0015] Preferably, the magnetic metal salt is one or a combination of two or more of cobalt salt, iron salt and nickel salt.

[0016] Preferably, when the magnetic metal salt is a combination of two salts, the molar ratio of the combination of the two salts is 0.1-10.

[0017] Preferably, in step S2, the immersion time is 6-24 hours, the drying temperature is 40-60° C., and the drying time is 8-12 hours.

[0018] Preferably, in step S3, the temperature is raised to the sintering temperature by gradient heating, and the specific process is: heating from room temperature to 300-400°C at a heating rate of 5-10°C / min, and then heating to the sintering temperature at a heating rate of 5-10°C / min. The protective atmosphere is argon or inert atmosphere.

[0019] A second object of the present invention is to provide a carbon composite absorbing material prepared by the method for preparing the carbon composite absorbing material described in any one of the above.

[0020] Further improvements as carbon composite absorbers:

[0021] Preferably, the carbon composite absorbing material is used in the fields of electromagnetic wave shielding and electromagnetic wave absorption.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1) The present invention provides a method for preparing a carbon composite absorbing material, which uses waste filter cotton as a raw material, soaks it in an alkaline solution for water bath treatment, removes the surface glue of the waste filter cotton, and then immerses it in a magnetic metal salt solution, and then sintered it at a high temperature to obtain a carbon composite absorbing material.

[0024] The excellent electromagnetic wave absorption performance of the composite absorbing material comes from the fact that the magnetic metal ions are uniformly loaded on the surface of the waste filter cotton during the preparation process, and then the waste filter cotton loaded with magnetic metal ions is sintered in an inert atmosphere to carbonize the waste filter cotton. At the same time, the magnetic metal ions undergo a carbon thermal reduction reaction and are converted into nano-metal single substances or alloy particles loaded on the surface of carbon. The appropriate amount of metal single substances or alloys on the surface of the composite absorbing material can effectively improve the electromagnetic impedance matching. At the same time, the rich heterogeneous interfaces in the composite absorbing material can form a large amount of interface polarization, and the polar groups and defects in the carbon matrix can lead to dipole polarization, which are conducive to improving the absorbing performance of the composite absorbing material.

[0025] The present invention adopts an impregnation method combined with heat treatment to prepare the composite wave absorbing material, and the preparation process is simple and easy, and the cost is low. The impregnation liquid used in the product preparation process can be recycled, and no complicated synthesis equipment and organic solvents are required, which is suitable for industrial production.

[0026] 2) The composite absorbing material prepared by the present invention not only has a thin matching thickness, a wide effective absorption bandwidth, and strong microwave absorption, but also has an absorption capacity that almost covers the X-band and Ku-band. Moreover, the electromagnetic parameters and absorbing performance can be adjusted by changing the concentration of the metal salt solution in the impregnation liquid, the sintering temperature or time, and the thickness of the matching layer, so as to meet the needs of different application environments. Minimum reflection loss RL min The absorption bandwidth of the composite wave absorbing material is -67.46dB, and the widest effective absorption bandwidth is 5.20GHz. Compared with carbon-based wave absorbing materials such as carbon nanotubes, carbon fibers and graphene, the waste filter cotton raw materials involved in the present invention are cheap and easy to obtain, and the preparation process is pollution-free. This low-cost and high-efficiency composite wave absorbing material can be widely used in the fields of electromagnetic shielding of wireless communication equipment, reducing signal reflection in radar systems, and constructing stealth materials for aerospace vehicles. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1is the XRD pattern of the CoFe / C composite absorbing material prepared in Example 4;

[0028] Figure 2 1 is a SEM image and an energy spectrum of the CoFe / C composite absorbing material prepared in Example 4;

[0029] Figure 3 is an electromagnetic parameter diagram of the CoFe / C composite absorbing material prepared in Example 4;

[0030] Figure 4 This is a 3D graph of the reflection loss of the CoFe / C composite absorbing material prepared in Example 4. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail in conjunction with the following embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. The waste filter cotton used in the following embodiments and comparative examples are all derived from the waste filter cotton generated during the maintenance of the motor vehicles of the Nanjing Branch of Shanghai Railway Locomotive and Rolling Stock Development Co., Ltd. The manufacturer of the air conditioning filter cotton is Shanghai Railway Vehicle High-tech Materials Jiangsu Co., Ltd., and the models are XK-200-L15, XK-200-L20 and XK-380B.

[0032] Example 1

[0033] This embodiment provides a method for preparing a carbon composite absorbing material, which specifically includes the following steps:

[0034] S1. Cut the waste filter cotton (model: XK-200-L15) into small pieces, soak them in 5wt% NaOH solution, and then place the soaking liquid in a 90℃ water bath for 6h. Take it out and wash it with deionized water until it is neutral, and dry it in a 60℃ forced air drying oven for 5h to obtain the pretreated waste filter cotton.

[0035] S2. Add 10.1 g of ferric nitrate nonahydrate into 50 mL of deionized water and stir magnetically until completely dissolved to obtain a magnetic metal salt solution with a concentration of 0.5 mol / L; add 1.0 g of pretreated waste filter cotton, let it stand and soak for 24 hours, then take it out and dry it, filter it and put it into a 60°C forced air drying oven to dry it for 10 hours to obtain a precursor;

[0036] S3. Place the precursor in a crucible, place the crucible in a tubular furnace, and heat the mixture from room temperature to 300°C at a heating rate of 5°C / min in a nitrogen atmosphere, then heat the mixture to 700°C at the same heating rate, sinter at this temperature for 2 hours, and cool naturally to room temperature to obtain a Fe / C composite absorbing material.

[0037] Using the coaxial method, the composite absorbing material and paraffin wax were mixed evenly at a mass ratio of 5.5:4.5 at 80 °C, and pressed into a paraffin ring with a thickness of d using a standard mold. The Agilent vector network analyzer was used to test the absorbing performance of paraffin rings of different thicknesses. The results are as follows: When the matching thickness d is 1.7 mm, the minimum reflection loss RL is achieved. min is -46.26dB, and the effective absorption bandwidth (RL<-10dB) is 3.12GHz; when the matching thickness d is 1.3mm, the effective absorption bandwidth can reach the widest value, which is 4.28GHz, and the minimum reflection loss RL min It is -25.99dB.

[0038] Example 2

[0039] This embodiment provides a method for preparing a carbon composite wave absorbing material. The specific steps are as described in Example 1, except that in step S2, 7.27 g of nickel nitrate hexahydrate is added to 50 mL of deionized water and stirred magnetically until completely dissolved, as a magnetic metal salt solution with a concentration of 0.5 mol / L. Finally, a Ni / C composite wave absorbing material is obtained.

[0040] The composite absorbing material and paraffin wax were mixed evenly at a mass ratio of 5.5:4.5 at 80°C, and pressed into paraffin wax rings of a certain thickness using a standard mold. The absorbing performance of paraffin wax rings of different thicknesses was calculated based on the electromagnetic parameters of the material. The results are as follows: When the matching thickness d is 1.5 mm, the minimum reflection loss RL is achieved. min It is -56.82dB, and the effective absorption bandwidth reaches the widest, which is 4.4GHz.

[0041] Example 3

[0042] This embodiment provides a method for preparing a carbon composite wave absorbing material. The specific steps are as described in Example 1, except that in step S2, 7.28 g of cobalt nitrate hexahydrate is added to 50 mL of deionized water and stirred magnetically until completely dissolved, as a magnetic metal salt solution with a concentration of 0.5 mol / L. Finally, a Co / C composite wave absorbing material is obtained.

[0043] The composite absorbing material and paraffin wax were mixed evenly at a mass ratio of 5.5:4.5 at 80°C, and pressed into paraffin wax rings of a certain thickness using a standard mold. The absorbing performance of paraffin wax rings of different thicknesses was calculated based on the electromagnetic parameters of the material. The results are as follows: When the matching thickness d is 3.3 mm, the minimum reflection loss RL is achieved. min is -47.39dB, and the effective absorption bandwidth is 1.72GHz; when the matching thickness d is 1.6mm, the effective absorption bandwidth can reach the widest value, which is 5.20GHz, and the minimum reflection loss RL min It is -21.92dB.

[0044] Example 4

[0045] This embodiment provides a method for preparing a carbon composite wave absorbing material. The specific steps are as described in Example 1, except that in step S2, 7.28 g of cobalt nitrate hexahydrate and 10.1 g of ferric nitrate nonahydrate are added to 50 mL of deionized water, and magnetic stirring is performed until they are completely dissolved, as a magnetic metal salt solution, the molar ratio of the two salts is 1:1, and the total concentration is 1.0 mol / L. Finally, a CoFe / C composite wave absorbing material is obtained.

[0046] The composite absorbing material and paraffin wax were mixed evenly at a mass ratio of 5.5:4.5 at 80°C, and pressed into paraffin wax rings of a certain thickness using a standard mold. The absorbing performance of paraffin wax rings of different thicknesses was calculated based on the electromagnetic parameters of the material. The results are as follows: When the matching thickness d is 1.7 mm, the minimum reflection loss RL is achieved. min is -67.46dB, and the effective absorption bandwidth is 3.76GHz; when the matching thickness d is 1.5mm, the effective absorption bandwidth can reach the widest value, which is 4.44GHz, and the minimum reflection loss RL min It is -39.29dB.

[0047] Example 5

[0048] This embodiment provides a method for preparing a carbon composite absorbing material, which specifically includes the following steps:

[0049] S1. Cut the waste filter cotton (model: XK-200-L20) into small pieces, soak them in 10wt% NaOH solution, and then place the soaking liquid in a 100℃ water bath for 6h. Take it out and wash it with deionized water until it is neutral, and dry it in an 80℃ air drying oven for 4h to obtain the pretreated waste filter cotton.

[0050] S2. Add 7.27 g nickel nitrate hexahydrate and 10.1 g ferric nitrate nonahydrate into 50 mL deionized water, stir magnetically until completely dissolved, and use the solution as a magnetic metal salt, wherein the molar ratio of the two salts is 1:1 and the total concentration is 1.0 mol / L; add 5.0 g pretreated waste filter cotton, let it stand and soak for 10 hours, then take it out and dry it, filter it and put it into a 60°C forced air drying oven and dry it for 8 hours to obtain a precursor;

[0051] S3. Place the precursor in a crucible, place the crucible in a tubular furnace, and heat the mixture from room temperature to 350°C at a heating rate of 8°C / min in a nitrogen atmosphere, and then heat the mixture to 900°C at a heating rate of 8°C / min. Sinter the mixture at this temperature for 1 hour, and cool the mixture naturally to room temperature to obtain a NiFe / C composite absorbing material.

[0052] The composite absorbing material and paraffin wax were mixed evenly at a mass ratio of 5.5:4.5 at 80°C, and pressed into paraffin wax rings of a certain thickness using a standard mold. The absorbing performance of paraffin wax rings of different thicknesses was calculated based on the electromagnetic parameters of the material. The results are as follows: When the matching thickness d is 1.8 mm, the minimum reflection loss RL is achieved. min is -53.17dB, and the effective absorption bandwidth is 3.52GHz; when the matching thickness d is 1.5mm, the effective absorption bandwidth can reach the widest value, which is 4.8GHz, and the minimum reflection loss RL min It is -32.21dB.

[0053] Example 6

[0054] This embodiment provides a method for preparing a carbon composite absorbing material, which specifically includes the following steps:

[0055] S1. Cut the waste filter cotton (model XK-380B) into small pieces, soak it in 8wt% NaOH solution, and then place the soaking liquid in a 90℃ water bath for 8h. Take it out and wash it with deionized water until it is neutral, and dry it in a 70℃ forced air drying oven for 5h to obtain the pretreated waste filter cotton.

[0056] S2. Add 7.27 g of nickel nitrate hexahydrate and 7.28 g of cobalt nitrate nonahydrate into 50 mL of deionized water, stir magnetically until completely dissolved, and use the solution as a magnetic metal salt solution. The molar ratio of the two salts is 1:1, and the total concentration is 1.0 mol / L. Add 2.0 g of pretreated waste filter cotton, let it stand and soak for 6 hours, then take it out and dry it. After filtering, put it in a 50°C forced air drying oven and dry it for 10 hours to obtain a precursor.

[0057] S3. Place the precursor in a crucible, place the crucible in a tubular furnace, and heat the mixture from room temperature to 400°C at a heating rate of 6°C / min in a nitrogen atmosphere, and then heat the mixture to 800°C at the same heating rate. Sinter the mixture at this temperature for 1.5 hours, and cool the mixture naturally to room temperature to obtain a NiCo / C composite absorbing material.

[0058] The composite absorbing material and paraffin wax were mixed evenly at a mass ratio of 5.5:4.5 at 80°C, and pressed into paraffin wax rings of a certain thickness using a standard mold. The absorbing performance of paraffin wax rings of different thicknesses was calculated based on the electromagnetic parameters of the material. The results are as follows: When the matching thickness d is 3.7 mm, the minimum reflection loss RL is achieved. min is -57.77dB, and the effective absorption bandwidth is 1.96GHz; when the matching thickness d is 1.2mm, the effective absorption bandwidth can reach the widest value, which is 2.44GHz, and the minimum reflection loss RL min It is -14.39dB.

[0059] Comparative Example 1

[0060] This comparative example provides a method for preparing a carbon absorbing material. The specific steps refer to those of Example 1, except that the waste filter cotton pretreated in step S1 is directly subjected to the operation of step S3 to obtain a waste filter cotton-derived carbon absorbing material.

[0061] The obtained absorbing material and paraffin were mixed evenly after being heated at 80°C in a mass ratio of 5.5:4.5, and pressed into paraffin rings of a certain thickness using a standard mold. The absorbing properties of paraffin rings of different thicknesses were tested using an Agilent vector network analyzer. The absorbing properties of paraffin rings of different thicknesses were calculated based on the electromagnetic parameters of the material. The results are as follows: It was found that there was no effective band in the absorbing performance.

[0062] Comparative Example 2

[0063] This comparative example provides a method for preparing a carbon composite absorbing material. The specific steps refer to Example 4, except that this comparative example is sintered at 600° C. for 2 hours to obtain a waste filter cotton derived carbon absorbing material.

[0064] The obtained composite absorbing material and paraffin were mixed evenly after being heated at 80°C in a mass ratio of 5.5:4.5, and pressed into paraffin rings of a certain thickness using a standard mold. The absorbing properties of paraffin rings of different thicknesses were tested using an Agilent vector network analyzer. The absorbing properties of paraffin rings of different thicknesses were calculated based on the electromagnetic parameters of the material. The results are as follows: It was found that there was no effective band in the absorbing performance.

[0065] Table 1 Comparison of the wave absorbing performance of the products of Examples 1-7 and Comparative Examples

[0066] <![CDATA[RL min (dB)]]> Widest effective absorption bandwidth (GHz) Example 1 -46.26 4.28 Example 2 -56.82 4.40 Example 3 -47.39 5.20 Example 4 -67.46 4.44 Example 5 -53.17 4.8 Example 6 -57.77 2.44 Comparative Example 1 -9.53 0 Comparative Example 2 -5.91 0

[0067] From the comparison of the absorbing performance of Examples 1-6 and Comparative Examples 1-2 in Table 1, it can be seen that in the embodiments, the waste filter cotton is pretreated and impregnated with loaded magnetic metal ions to obtain a precursor, and then the precursor is sintered to obtain a composite absorbing material, which has excellent absorbing performance. This is because the waste filter cotton is carbonized to form a carbon conductive network structure after heat treatment, and the magnetic metal ions form nano-metal simple substances or alloy particles on the surface of the carbon. The appropriate content of nano-metal simple substances or alloy particles can effectively improve the electromagnetic impedance matching. In addition, the interweaving of the carbon conductive network structure not only triggers multiple scattering and reflection of the incident electromagnetic waves, but also prolongs the dissipation path of the electromagnetic wave energy. More importantly, a large number of interfaces are formed between the components of the composite absorbing material, which promotes the transfer of space charges and leads to interface polarization. The polar groups and defects in the carbon matrix can serve as the polarization center of the dipole, resulting in dipole polarization, thereby effectively improving the absorbing performance of the composite material. In contrast, the materials prepared in Comparative Examples 1-2 have poor absorbing performance. This is because the material obtained in Comparative Example 1 is a single carbon material with a high dielectric constant, resulting in poor impedance matching, which causes electromagnetic waves to be strongly reflected on its surface and unable to enter the interior of the material for effective absorption, so the wave absorption performance is poor; and the sintering temperature in Comparative Example 2 is lower than the graphitization temperature of the waste filter cotton, and the prepared material has poor conductivity and low dielectric loss, which makes the material unable to effectively attenuate electromagnetic waves.

[0068] Figure 1 is the XRD pattern of the composite absorbing material prepared in Example 4 of the present invention; Figure 2 1 is a SEM image and an energy spectrum image of the composite absorbing material prepared in Example 4 of the present invention; Figure 3 is an electromagnetic parameter diagram of a composite absorbing material prepared in Example 4 of the present invention; Figure 4 It is a 3D diagram of the reflection loss of the composite absorbing material prepared in Example 4 of the present invention.

[0069] Combination Figure 1 and Figure 2 The test results show that the waste filter cotton is converted into C, Co 2+ and Fe 3+ After carbothermal reduction, it is converted into CoFe alloy and uniformly loaded on the C surface.

[0070] Depend on Figure 3 The test results of the composite absorbing material prepared in Example 4 show that the real part ε' of the dielectric constant decreases with increasing frequency, which can be attributed to the influence of the dipole on the dielectric constant in the high-frequency range and the enhanced dispersion effect. The real part μ' and imaginary part μ" of the magnetic permeability are in the range of 1 and 0, respectively, showing weak magnetism. It can be seen from the loss tangent value that in the entire frequency range, the dielectric loss tangent value tanδ ε Greater than the magnetic loss tangent tanδμ , indicating that the absorbing performance of the composite absorbing material prepared in Example 4 mainly depends on the dielectric loss.

[0071] Depend on Figure 4 The test results of the composite absorbing material prepared in Example 4 show that the composite absorbing material has excellent microwave absorption performance, and the minimum reflection loss RL is achieved when the matching thickness d is 1.7 mm. min , the value is -67.46dB; the composite absorbing material prepared in Example 1 is also tested, and the minimum reflection loss RL is achieved when the matching thickness is 1.7mm min , the value is -46.26dB; the composite absorbing material prepared in Example 2 is also tested, and the minimum reflection loss RL is achieved when the matching thickness is 1.5mm min , the value is -56.82dB; the composite absorbing material prepared in Example 3 is also tested, and the minimum reflection loss RL is achieved when the matching thickness is 3.3mm min , the value is -47.39dB; the composite absorbing material prepared in Example 5 is also tested, and the minimum reflection loss RL is achieved when the matching thickness is 2.4mm min , the value is -46.17dB; the composite absorbing material prepared in Example 6 is also tested, and the minimum reflection loss RL is achieved when the matching thickness is 1.8mm min , its value is -53.17dB; the composite absorbing material prepared in Example 7 is also tested, and the minimum reflection loss RL is achieved when the matching thickness is 3.7mm min The test results show that the composite wave absorbing materials prepared in Examples 1-7 can absorb electromagnetic waves by more than 99.99%.

[0072] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a carbon composite absorbing material, characterized in that: The steps include: S1, cutting the waste filter cotton into small pieces, soaking it in an alkaline solution and treating it in a water bath, then taking out the treated waste filter cotton, washing it with deionized water several times until it is neutral, and drying it to obtain pretreated waste filter cotton; S2, prepare a magnetic metal salt solution, add the pretreated waste filter cotton, let it stand and soak evenly, then take it out and dry it to obtain a precursor; S3. Place the precursor in a protective atmosphere, sinter at 600°C-900°C for 1-2 hours to obtain a composite absorbing material.

2. The method for preparing the carbon composite absorbing material according to claim 1, characterized in that: The alkaline solution is one of sodium hydroxide and potassium hydroxide, and the concentration is 5wt%-10wt%.

3. The method for preparing the carbon composite absorbing material according to claim 1, characterized in that: The water bath temperature is 80-100°C for 6-10 hours, and the drying temperature is 40-80°C for 4-10 hours.

4. The method for preparing a carbon composite absorbing material according to claim 1, characterized in that: The concentration of the magnetic metal salt is 0.1-1 mol / L, and the amount of pretreated waste filter cotton added to the magnetic metal salt solution is 0.01-0.1 g / ml.

5. The method for preparing a carbon composite absorbing material according to claim 1, characterized in that: The magnetic metal salt is one or a combination of two or more of cobalt salt, iron salt and nickel salt.

6. The method for preparing the carbon composite absorbing material according to claim 5, characterized in that: When the magnetic metal salt is a combination of two salts, the molar ratio of the combination of the two salts is 0.1-10.

7. The method for preparing a carbon composite absorbing material according to claim 1, characterized in that: In step S2, the immersion time is 6-24 hours, the drying temperature is 40-60° C., and the drying time is 8-12 hours.

8. The method for preparing a carbon composite absorbing material according to claim 1, characterized in that: In step S3, the temperature is raised to the sintering temperature by gradient heating, and the specific process is: the temperature is raised from room temperature to 300-400°C at a heating rate of 5-10°C / min, and then the temperature is raised to the sintering temperature at a heating rate of 5-10°C / min. The protective atmosphere is argon or an inert atmosphere.

9. A carbon composite microwave absorbing material obtained by the method for preparing a carbon composite microwave absorbing material according to any one of claims 1 to 8.

10. The carbon composite absorbing material according to claim 9, characterized in that: The carbon composite wave absorbing material is used in the fields of electromagnetic wave shielding and electromagnetic wave absorption.

Citation Information

Patent Citations

  • Method for preparing natural-cellulose based magnetic porous carbon and application of natural-cellulose based magnetic porous carbon

    CN106179200A

  • Magnetic wave-absorbing fabric, and preparation method and application thereof

    CN108951192A

  • Electromagnetic wave shielding composite material

    CN111171553A

  • Wave-absorbing material derived from NiCo-MOF / biomass cotton and preparation method thereof

    CN113912038A

  • Composite wave-absorbing material and preparation method thereof

    CN117143562A